2007
DOI: 10.1016/j.ymben.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the methylmalonyl-CoA metabolite node of Saccharopolyspora erythraea for increased erythromycin production

Abstract: Engineering of the methylmalonyl-CoA (mmCoA) metabolite node of the Saccharopolyspora erythraea wild type strain (FL2267) through duplication of the mmCoA mutase (MCM) operon led to a 51% (range 40%-64%, 0.95 CI, N = 152) increase in erythromycin production in a highperformance oil-based fermentation medium. The MCM operon was carried on a 6.8 kb DNA fragment in plasmid pFL2212 which was inserted by homologous recombination into the S. erythraea chromosome. The fragment contained one uncharacterized gene, ORF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 38 publications
1
57
0
1
Order By: Relevance
“…151 Recently, engineering S. erythraea through duplication of the methylmalonyl-CoA mutase led to a 50% increase in erythromycin production. 152 Moreover, glucose or glycerol inhibits S-adenosylmethionine erythromycin O-methyl transferase activity. Reeve and Baumberg 153 measured the effect of glucose on the transcription of the eryAI gene, encoding the type I polyketide synthase.…”
Section: Streptomycesmentioning
confidence: 99%
“…151 Recently, engineering S. erythraea through duplication of the methylmalonyl-CoA mutase led to a 50% increase in erythromycin production. 152 Moreover, glucose or glycerol inhibits S-adenosylmethionine erythromycin O-methyl transferase activity. Reeve and Baumberg 153 measured the effect of glucose on the transcription of the eryAI gene, encoding the type I polyketide synthase.…”
Section: Streptomycesmentioning
confidence: 99%
“…Although tedious and time-consuming, the strategy can increase titers 10-to 100-fold (1). In rational engineering, knowledge of biochemical pathways guides genetic manipulations to increase titers, such as through modification of the methylmalonyl-CoA metabolite node (2). Often, overexpression of a gene that regulates the biosynthetic cluster of an antibiotic increases titers.…”
mentioning
confidence: 99%
“…Previous studies have shown that antibiotics production can be enhanced by increasing precursors. [24][25][26] In this study,one metabolic distinction among the three strains was a remarkable accumulation of acetyl-CoA in WH124 during the middle stage of the fermentation process (Fig. 4c).…”
Section: Discussionmentioning
confidence: 61%